Leaf-level responses of olive trees (Olea europaea) to the suspension of irrigation during the winter in an arid region of Argentina - Rousseaux, Maria Cecilia (2008)
Irrigation is normally suspended during the winter months in the Mediterranean where olive is traditionally cultivated because rainfall is high and reference evapotranspiration (ETo) is low under the fairly cold and cloudy winter conditions in this region. In contrast, the semi-arid and arid provinces of northwestern Argentina receive little, if any, winter precipitation and daily values of ETo are higher than in the Mediterranean. To evaluate the range of winter irrigation strategies currently employed in northwestern Argentina, we assessed leaf-level responses of olive trees to two very contrasting irrigation regimes, no irrigation versus a highly irrigated regime (crop coefficient >1.0), in La Rioja, Argentina. After 15 d, both soil volumetric water content and leaf water potential were substantially lower in the unirrigated treatment. These differences in leaf water potential were consistent through to the end of the 40 d experiment with recovery occurring within a week of rewatering. Only small reductions in leaf gas exchange parameters including transpiration and leaf conductance (gl) were observed after 40 d without irrigation. Independent of the irrigation level, there was a strong relationship between gl and atmospheric vapor pressure deficit (VPD), with gl decreasing in an apparently curvilinear manner as VPD increased. Quantum efficiency of Photosystem II was only reduced by irrigation suspension on 1 d of measurement. These preliminary results suggest that only mild water stress occurred during the winter in trees that were not irrigated for 6-7 weeks in arid La Rioja, Argentina although further research over several years is needed to determine a crop coefficient for the winter months.